INDIRECT VALVE REGULATION IN MULTICHAMBER HYDROMECHANICAL SYSTEMS - V. I. ANTONENKO; V. S. SIDORENKO (Advanced Engineering Research, 2010)
The results of the theoretical and experimental research of the original synchronized dualchambered hydromechanical system with indirect regulated valve systems of different structural configuration are shown.